A Language Production In Children With Dysarthria Language Disorder: A Psycholinguistic Study - Rasya Risyafa Putri (Modality Journal: International Journal of Linguistics and Literature, 2024)
The process of language production can be impeded by various language disorders, one of which is dysarthria. Dysarthria is a condition characterized by abnormalities in the nervous system that affect the functioning of the articulatory muscles or speech organs, leading to uncertain pronunciation of both vowel and consonant phonemes. This study aims to reveal the form of language production in children with dysarthria and analyze the types of errors in their language production. The research is grounded in psycholinguistic theory and employs the error classification theories of McCaffrey (2008), M. F. Berry, and John Bisension to analyze language disorder errors. A descriptive qualitative method is used, with data sourced from speech sound production in children with dysarthria. Data collection techniques include interviews and pronunciation tests. Data analysis follows the Miles and Huberman (1994) framework, encompassing data reduction, data display, and conclusion drawing. Findings indicate that language production in children with dysarthria is marked by unclear articulation, weak voice, rapid speech tempo, and difficulties in phoneme pronunciation. Error types identified include phoneme distortion, omission, and substitution. Abstrak Proses produksi bahasa dapat terhambat oleh berbagai gangguan bahasa, salah satunya adalah disartria. Disartria adalah kondisi yang ditandai dengan kelainan pada sistem saraf yang mempengaruhi fungsi otot artikulator atau organ bicara, yang mengakibatkan ketidakpastian dalam pengucapan fonem vokal maupun konsonan. Penelitian ini bertujuan untuk mengungkap bentuk produksi bahasa pada anak-anak dengan disartria dan menganalisis jenis kesalahan dalam produksi bahasa mereka. Penelitian ini berlandaskan teori psikolinguis dan menggunakan teori klasifikasi kesalahan gangguan bahasa dari McCaffrey (2008), M. F. Berry, dan John Bisension untuk menganalisis kesalahan gangguan bahasa. Metode yang digunakan adalah metode kualitatif deskriptif, dengan sumber data dari produksi suara bicara pada anak-anak dengan disartria. Teknik pengumpulan data mencakup wawancara dan tes pengucapan. Analisis data mengikuti kerangka kerja Miles dan Huberman (1994), meliputi reduksi data, tampilan data, dan penarikan kesimpulan. Temuan penelitian menunjukkan bahwa produksi bahasa pada anak-anak dengan disartria ditandai dengan artikulasi yang tidak jelas, suara yang lemah, tempo bicara yang cepat, dan kesulitan dalam pengucapan fonem. Jenis kesalahan yang diidentifikasi meliputi distorsi fonem, penghilangan fonem, dan substitusi fonem. Kata Kunci: produksi bahasa, disartria, psikolinguistik.